Non-dispersive UV Absorption Spectroscopy: A Promising New Approach for in-situ Detection of Sulfur Dioxide - Tirpitz, Jan-Lukas; Pöhler, Denis; Bobrowski, Nicole; Christenson, Bruce; Rüdiger, Julian; Schmitt, Stefan; Platt, Ulrich (Frontiers in Earth Science, 2019)
A new type of instrument for in-situ detection of volcanic sulfur dioxide is presented on the basis of non-dispersive UV absorption spectroscopy. It is a promising alternative to presently used compact and low-cost SO2 monitoring techniques, over which it has a series of advantages, including an inherent calibration, fast response times (< 2 s to reach 90 % of the applied concentration), a measurement range spanning about 5 orders of magnitude and small, well known cross sensitivities to other gases. Compactness, cost-efficiency and detection limit (< 1 ppm, few ppb under favourable conditions) are comparable to other presently used in-situ instruments. Our instrument prototype has been extensively tested in comparison studies with established methods. In autumn 2015, diverse volcanic applications were investigated such as fumarole sampling, proximal plume measurements and airborne measurements several kilometers downwind from the vent on Mt. Etna and White Island. General capabilities and limitations of the measurement principle are discussed, considering different instrument configurations and future applications.